Biopolymer‐Based Polyelectrolyte Nanoplatforms for Targeted Photodynamic Therapy of Breast Cancer - Athira Narayanan; Benedetta di Chiara Stanca; Daniela Pinheiro; Laura Giannotti; Fabrizio Damiano; André Ferreira Moreira; Sónia Miguel; Leonardo Lamanna; Eleonora Stanca; Maria Grazia Raucci; Gianpiero Colangelo; Luisa Siculella; et al. (VIEW, 2026)
Abstract Nanomedicine has reshaped healthcare, especially in targeted drug delivery systems (DDSs) and diagnostics, addressing the limitations of traditional cancer therapies. Integration of photodynamic therapy (PDT) with nanoparticle‐based DDSs has significantly improved the targeted accumulation and pharmacokinetic properties of photosensitizers within tumor cells, enabling selective tumor cell death while sparing healthy tissues. This study developed chitosan‐sericin polyelectrolyte nanoparticles (CSSN NPs) via the Flash nanocomplexation (FNC) technique to enhance the 5‐aminolevulinic acid (5‐ALA) delivery, a precursor of protoporphyrin IX (PpIX), and evaluated their potential in PDT against the MCF‐7 breast cancer cell line. The 5‐ALA‐loaded CSSN NPs exhibited a hydrodynamic diameter ≤100 nm, a positive surface charge, and an encapsulation efficiency of ∼92% with a controlled release profile in acidic environments. In vitro assays demonstrated a ∼40% reduction in cell viability compared with free 5‐ALA, further confirmed by elevated red fluorescence observed in the Calcein/Propidium iodide assay. Confocal microscopy revealed strong PpIX red fluorescence and increased perinuclear accumulation, indicating effective cellular uptake. PpIX phototoxicity was validated by reactive oxygen species induction upon irradiation. These innovative biopolymer‐based DDSs demonstrate considerable potential in enhancing the therapeutic efficacy of 5‐ALA and improving PDT outcomes, setting the stage for future advancements in targeted cancer therapies.